Water quality Parameters in Sindphana dam near Shirur Kasar, Beed District, Maharashtra State, India (Bangladesh Journal of Zoology, 2022)
Water analysis is essential to preserve and protect the natural ecosystem, which depends on their physical, chemical and biological characteristics; these are directly linked with human welfare. This study was evaluated the physicochemical features of water and their relationships in Sindphana Dam near Shirur Kasar, Breed district, Maharashtra state, India between January and December 2012. This study shows the water quality parameters were fluctuated during the summer, monsoon and winter seasons in Sindphana Dam. In this study, air temperature was positively related to water temperature, transparency and pH while it was negatively related to electric conductivity and dissolved oxygen (DO). The water temperature was positively related to air temperature, transparency and pH, while it was negatively related to electric conductivity and DO. Water transparency also negatively related to turbidity, electric conductivity, biochemical oxygen demand (BOD) and chemical oxygen demand (COD). Electric conductivity was positively related to turbidity, BOD and COD. The pH was negatively related to electric conductivity, DO, BOD and COD. The study indicated that the Sindphana Dam water quality parameters were acceptable limits for aquatic biota.Bangladesh J. Zool. 49 (3): 403-410, 2021